Pornocracy - Breillat, Catherine 1948- (Semiotext(e) native agents, 2008)
A beautiful woman wanders through a gay disco and engages a man, confident that he will follow her. Perversely and dispassionately, she offers her body as the ground of a ritualistic game in which, over the course of three evenings, the two explore the numbing mechanics of sexual brutality. - Adapted and directed for film by Breillat as 'Anatomy of Hell' (2004).